A Field Experiment in Motivating Employee Ideas - Gibbs, Michael; Neckermann, Susanne; Siemroth, Christoph (The Review of Economics and Statistics, 2017)
We study a field experiment at a large technology company. Employees were encouraged to submit ideas on process and product improvements. The company randomly assigned nineteen teams into treatment and control groups. Treatment team employees received rewards if their ideas were approved. Nothing changed for control team employees. Our main finding is that rewards substantially increased the quality of ideas. Rewards increased participation in the suggestion system but decreased ideas per participating employee, with no net effect on the quantity of ideas. Broader participation persisted after the reward was discontinued, suggesting habituation. We find no evidence for motivational crowding out.